Archaeology and the Sugpiaq renaissance on Kodiak Island: Three stories from Alaska - Pullar, Gordon; Knecht, Richard; Haakanson, Sven (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2013)
The Sugpiat people have lived in the Kodiak Archipelago for at least 7,500 years, but suffered extraordinary pressure on their cultural identity beginning with violent Russian conquest in 1784 and followed by Russian and American colonisation. Recognising that drastic actions were needed to preserve Sugpiaq heritage, the Kodiak Area Native Association began a cultural revitalisation movement. The centrepiece was a Native-owned state-of-the-art museum that opened in 1995. This essay recounts the stories of three participants in the beginning of a process that has transformed the cultural landscape of Kodiak.